EVALUATION OF TRANSGENIC INDICA RICE (Oryza sativa L.) THROUGH REPORTER AND DESIRED GENE - Prodhan, Shamsul H.; Nagamiya, K.; Komamine, A.; Morishima, H. (Bangladesh Journal of Plant Breeding and Genetics, 2007)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 10.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "MS Mincho"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Rice is one of the most important food crops in the world. It is greatly affected by various abiotic stresses. Among them, to improve the complex stress salinity <span style="font-size: 10.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "MS Mincho"; mso-font-kerning: 1.0pt; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;">we introduced a desired gene katE, a catalase gene of Escherichia coli, and reporter gene GUS into the indica rice cultivar Kasalath. Plant survival under different salt water concentration was checked. Transformation was carried out using Agrobacterium tumefaciens strain EHA101 harboring a binary vector pIES6/Hm/katE and pIG121/ Hm/ GUS which contains genes for catalase katE, GUS gene, hygromycine resistance gene HPT and kanamycine resistance gene NPTII in the T-DNA region. Transformation was confirmed by PCR with katE and GUS primer. Transgenic plants at very young stage (3 days) were able to grow up to 15 days in 100 mM NaCl solution and 7 days in 250 mM NaCl solution where as non transgenic plants could not survive even up top 5 days in 100 mM condition and 7 days in 250 mM NaCl concentration. Twenty eight days matured plants could survive and were able to form iflorescence. Here a single gene introduction significantly improved the salt tolerance of this crop rice. DOI: http://dx.doi.org/10.3329/bjpbg.v20i2.17029